Evaluation of Bursal Index and Bursal Lesion Scores in Broiler Flocks - Zahedi, A; Jamshidi, K; Poorghasemi, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Background and Aims: The bursa of Fabricius (BF) is recognized as a vital organ that plays a crucial role in birds immunity. In order to determine the immunological status of the birds, this study was conducted to evaluate the bursal index, and bursal lesion scores in broilers. Materials and Methods: Therefore, a total of 200 broilers, 35-45 days of age, from 10 broiler flocks were randomly selected, weighed, then sacrificed. At necropsy, the bursa of Fabricius were obtained, examined, and weighed. Bursal index (BI) was calculated. Representative pieces of tissues from bursa of Fabricius were preserved in 10% neutral buffer formaldehyde for further histopathological evaluation. Results: The results obtained from (BI) calculated during the study period for all 22 broiler farms, revealed that more than 81% of the birds were included in bad group and less than 19% in mediocre group. Degree of microscopic lesions between different groups and even within one group varied from 0 (normal) to 5 (atrophy of BF) and included lymphoid necrosis in follicles, hyperplasia and folding of bursal inner epithelium, and formation of fibrous connective tissue within the follicles. Average bursal lesion scores for all groups under study was recorded as 2.09%. Conclusions: On the basis of all results including (BI) and bursal lesion scores it is concluded that bursal lymphoid structures suffer various degree of pathological lesions indicating suppressed immunity in broiler farms along with poor performance.